2003
DOI: 10.1051/0004-6361:20030622
|View full text |Cite
|
Sign up to set email alerts
|

Hot HB stars in globular clusters – Physical parameters and consequences for theory

Abstract: Abstract. We present the results of spectroscopic analyses of hot horizontal branch (HB) stars in M 13 and M 3, which form a famous "second parameter" pair. From the spectra and Strömgren photometry we derived -for the first time in M 13 -atmospheric parameters (effective temperature and surface gravity). For stars with Strömgren temperatures between 10 000 and 12 000 K we found excellent agreement between the atmospheric parameters derived from Strömgren photometry and those derived from Balmer line profile f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
165
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(186 citation statements)
references
References 94 publications
21
165
0
Order By: Relevance
“…21), with hints of a slight rise, no more than 0.5 dex on average, among the hottest stars of M13 and M15. This pattern of overabundant iron and normal magnesium that we observe in our stars matches the prior results of Glaspey et al (1989) and the recent work by Moehler et al (1999) on the southern metal-poor globular NGC 6752. Moehler et al observe 42 BHB stars at medium spectral resolution and derive [Fe/H] and [Mg/H] from the strongest lines of each species.…”
Section: à0561supporting
confidence: 92%
See 3 more Smart Citations
“…21), with hints of a slight rise, no more than 0.5 dex on average, among the hottest stars of M13 and M15. This pattern of overabundant iron and normal magnesium that we observe in our stars matches the prior results of Glaspey et al (1989) and the recent work by Moehler et al (1999) on the southern metal-poor globular NGC 6752. Moehler et al observe 42 BHB stars at medium spectral resolution and derive [Fe/H] and [Mg/H] from the strongest lines of each species.…”
Section: à0561supporting
confidence: 92%
“…Underabundances of helium have been observed previously in many hot, evolved stars, including subdwarf B (sdB) stars in the field and the analogous EHB stars in globular clusters (Baschek 1975, p. 101;Heber 1987;Moehler et al 2000). Michaud, Vauclair, & Vauclair (1983), building on the original suggestion by Greenstein, Truran, & Cameron (1967), explained these underabundances as a result of gravitational settling of helium.…”
Section: Explaining the Abundance Variationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous experience with the analysis of hot stars in globular clusters has shown that low surface gravities are often associated with impossibly small HB masses, thus indicating that the surface gravities are not reliable. To carry out this consistency check, we have estimated masses for all of our target stars using the approach outlined by Moehler et al (2000). Figure 6 compares these masses with the theoretical ZAHB masses for both canonical and helium-rich compositions.…”
Section: Cool Blue Tail Stars Near 10 000 Kmentioning
confidence: 99%